Trehalose/hyaluronate eyedrop effects on ocular surface inflammatory markers and mucin expression in dry eye patients - Fariselli C (Dove Medical Press, 2018)
Chiara Fariselli, Giuseppe Giannaccare, Michela Fresina, Piera Versura Ophthalmology Unit, Department of Experimental, Diagnostic and Specialty Medicine, School of Medicine (DIMES), Alma Mater Studiorum University of Bologna and St Orsola-Malpighi Teaching Hospital, Bologna, Italy Aim: To assess the ocular surface parameters, inflammatory marker level in tears, and mucin expression in conjunctival epithelium before and after treatment with trehalose/hyaluronate tear substitute in dry eye (DE) patients.Patients and methods: Fifteen DE patients were evaluated in an open-label, pilot study at enrollment, after 2 days of washout (baseline) and after 1 and 2 months (endpoint) of treatment with a trehalose/hyaluronate tear substitute (one drop/eye/three times daily). Data for symptoms of discomfort (Ocular Surface Disease Index and Visual Analogue Scale pain score), tear film (Schirmer test I, tear film breakup time), ocular surface damage (corneal National Eye Institute) and conjunctival van Bijsterveld scores, impression cytology scored by Nelson’s grade and goblet cells (GCs) number/mm2 analysis, and MUC4 immunostaining, and inflammation (interleukin [IL]-1β, IL-6, and IL-8 levels) were measured.Results: Significant changes at endpoint as compared to baseline were found for Ocular Surface Disease Index score (respectively, mean±SD, 22.2±2.9 vs 38.7±12.7), Visual Analogue Scale score (3.4±1.3 vs 6.6±1.4), tear film breakup time (8.6±1.28 vs 6.17±1.9 seconds), corneal staining (National Eye Institute grade 1.23±0.64 vs 3.37±0.49), conjunctival staining (1.73±1.14 vs 4.17±0.91), impression cytology (Nelson grade 1.10±0.20 vs 1.63±0.54), and GC density (139.9±22.0 vs 107.8±16.2 GC/mm2). IL-1β, IL-6, and IL-8 tear levels showed a significant decrease at endpoint as compared to baseline (respectively, pg/mL tears: 12.3±6.9, 26.6±25.2, 743.5±477.7 vs 33.6±17.3, 112.0±24.3, 1,139.2±671.7).Conclusions: A decrease in ocular discomfort symptoms, surface damage, and tear cytokine levels was shown after 2 months’ treatment with trehalose/hyaluronate tear substitute in DE patients, along with a significant GC density recovery. These results may be associated with the synergic action of both trehalose and hyaluronic acid in targeting different entries of the DE vicious loop. Keywords: dry eye, trehalose, hyaluronic acid, tear substitute, inflammation